Risk Factors for Fracture in Middle‐Age and Older‐Age Men of African Descent. (January 2014) - Sheu, Yahtyng; Cauley, Jane A; Patrick, Alan L; Wheeler, Victor W; Bunker, Clareann H; Zmuda, Joseph M
ABSTRACT Although fracture rates are lower in individuals of African descent compared to individuals of European ancestry, morbidity and mortality following a fracture may be greater in individuals of African ancestry. However, fracture risk and associated clinical risk factors have not been well‐defined among African ancestry populations, especially among men of African ancestry. We used data collected from the Tobago Bone Health Study to examine potential clinical risk factors for incident fractures, including demographic information, anthropometric measurements, medical history, lifestyle factors, bone mineral density (BMD), and hip structural geometry. Among 1933 Afro‐Caribbean men aged ≥40 years at study entry (mean age: 57.2 ± 11.0 years), 65 reported at least one new fracture during 10 years of subsequent follow‐up. Younger age, mixed Afro‐Caribbean ancestry, prior fracture history, BMD, and hip structural geometry were statistically significant risk factors for incident fractures. A 1‐SD change in several skeletal parameters (hip BMD, cross‐sectional area, outer diameter, cortical thickness, and buckling ratio) were each associated with a 35% to 56% increase in incident fracture risk after adjusting for age. Men with a prior fracture history were three times more likely to experience a new fracture during follow‐up, and the association remained strong after adjusting for age, mixed Afro‐Caribbean ancestry, and skeletal parameters (hazard ratios ranged from 2.72 to 2.82). Our findings suggest that except for age, risk factors for fracture in men of African ancestry are similar to established risk factors in white populations. Prior fracture history is a powerful and independent risk factor for incident fractures among men of African ancestry and could easily be incorporated into clinical risk evaluation. © 2014 American Society for Bone and Mineral Research.